Plasma lysosphingolipids in GRN-related diseases: Monitoring lysosomal dysfunction to track disease progression - Walid Khrouf; Dario Saracino; Benoit Rucheton; Marion Houot; Fabienne Clot; Daisy Rinaldi; Joana Vitor; Marie Huynh; Evelyne Heng; Dimitri Schlemmer; Florence Pasquier; Vincent Deramecourt; et al. (Neurobiology of Disease, 2023)
GRN mutations are among the main genetic causes of frontotemporal dementia (FTD). Considering the progranulin involvement in lysosomal homeostasis, we aimed to evaluate if plasma lysosphingolipids (lysoSPL) are increased in GRN mutation carriers, and whether they might represent relevant fluid-based biomarkers in GRN-related diseases.We analyzed four lysoSPL levels in plasmas of 131 GRN carriers and 142 non-carriers, including healthy controls and patients with frontotemporal dementias (FTD) carrying a C9orf72 expansion or without any mutation. GRN carriers consisted of 102 heterozygous FTD patients (FTD-GRN), three homozygous patients with neuronal ceroid lipofuscinosis-11 (CLN-11) and 26 presymptomatic carriers (PS-GRN), the latter with longitudinal assessments. Glucosylsphingosin d18:1 (LGL1), lysosphingomyelins d18:1 and isoform 509 (LSM18:1, LSM509) and lysoglobotriaosylceramide (LGB3) were measured by electrospray ionization-tandem mass spectrometry coupled to ultraperformance liquid chromatography.Levels of LGL1, LSM18:1 and LSM509 were increased in GRN carriers compared to non-carriers (p < 0.0001). No lysoSPL increases were detected in FTD patients without GRN mutations. LGL1 and LSM18:1 progressively increased with age at sampling, and LGL1 with disease duration, in FTD-GRN. Among PS-GRN carriers, LSM18:1 and LGL1 significantly increased over 3.4-year follow-up. LGL1 levels were associated with increasing neurofilaments in presymptomatic carriers.This study evidences an age-dependent increase of β-glucocerebrosidase and acid sphingomyelinase substrates in GRN patients, with progressive changes as early as the presymptomatic phase. Among FTD patients, plasma lysoSPL appear to be uniquely elevated in GRN carriers, and thus might serve as suitable non-invasive disease-tracking biomarkers of progression, specific to the pathophysiological process. Finally, this study might add lysoSPL to the portfolio of fluid-based biomarkers, and pave the way to disease-modifying approaches based on lysosomal function rescue in GRN diseases.